A modified XY model of transformer oil–paper insulation system including non‐uniform aging and conductance effect. Issue 13 (23rd March 2021) - Fan, Xianhao; Liu, Jiefeng; Zhang, Yiyi; Yang, Shichang; Zhang, Chaohai; Zhang, Yubo
Abstract: The accuracy and feasibility of the traditional XY model of transformer oil–paper insulation system are disputable since it ignored the effect of non‐uniform aging and conductance on dielectric response property. Given this issue, this work attempted to report a modified XY model to overcome these defects. The novelty of this work is in the exploration of the modified XY model as a potential tool for establishing the quantitative correlation among the complex relative permittivity of the liquid insulation, solid insulation, and liquid–solid composite insulation. In that respect, the presented verification experiments proved the feasibility and accuracy of the reported model. The contributions are expected to provide a theoretical basis for the condition evaluation of transformer solid insulation under non‐uniform aging conditions.